Regulatory assessment of nano-enabled health products in public health interest. Position of the scientific advisory board of the French National Agency for the Safety of Medicines and Health Products - Wahiba Oualikene-Gonin; Valérie Sautou; Eric Ezan; Henri Bastos; Eric Bellissant; Laëtitia Belgodère; Patrick Maison; Patrick Maison; Patrick Maison; Joël Ankri; The Scientific Advisory Board of the ANSM; Joël Ankri; et al. (Frontiers Media S.A., 2023)
Nanomaterials are present in a wide variety of health products, drugs and medical devices and their use is constantly increasing, varying in terms of diversity and quantity. The topic is vast because it covers nanodrugs, but also excipients (that includes varying proportions of NMs) and medical devices (with intended or not-intended (by-products of wear) nanoparticles). Although researchers in the field of nanomedicines in clinical research and industry push for clearer definitions and relevant regulations, the endeavor is challenging due to the enormous diversity of NMs in use and their specific properties. In addition, regulatory hurdles and discrepancies are often cited as obstacles to the clinical development of these innovative products. The scientific council of the Agence Nationale de Sécurité du Médicament et des produits de santé (ANSM) undertook a multidisciplinary analysis encompassing fundamental, environmental and societal dimensions with the aim of identifying topics of interest for regulatory assessment and surveillance. This analysis allowed for proposing some recommendations for approximation and harmonization of international regulatory practices for the assessment of the risk/benefit balance of these products, considering as well the public expectations as regards efficacy and safety of nanomaterials used in Health products, in terms of human and environmental health.